Adaptive controllers for an implantable insulin delivery system in type I diabetes patioent - (:unkn) unknown (Bhubaneswar, 2018)
page attached
Type 1 Diabetes patient
Keywords: Clinical Pre Clinical and Health; Insulin, Type 1 Diabetes patient